The putative promoter of a Xenopus laevis ribosomal gene is reduplicated. - Moss, T (Nucleic Acids Res, 1979)
With the aid of a novel poly-dA tailing-partial restriction technique and S1-protection mapping, the 5' terminal coding sequence for the 40S precursor ribosomal RNA of Xenopus laevis has been exactly identified. Since the promoter sequence for the 40S RNA should lie close to its 5' terminal coding sequence, we are able to conclude that the "Bam-Island" sequence reduplication (1) almost certainly represents a promoter reduplication. IMAGES: